TINJAUAN LITERATUR SISTEMATIS PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMK - Ningrum, Dwika Sulistia; Giatman, M.; Yuliarma, Yuliarma; Mardizal, Jonni; Aryasandy, Nensy (Jurnal Manajemen Pendidikan, 2025)
This study aims to systematically review the influence of principals’ leadership styles and work motivation on teachers’ performance in vocational high schools (SMK) in Indonesia. A Systematic Literature Review (SLR) approach was applied following the PRISMA 2020 guidelines. Thirty peer-reviewed journal articles published between 2020 and 2025 were collected from Google Scholar and Publish or Perish based on inclusion criteria emphasizing vocational education context and the examination of at least two core variables. The synthesis results reveal that leadership styles have a positive and significant effect on teachers’ performance, while work motivation emerges as a key determinant driving teachers’ responsibility, professionalism, and creativity. Both variables show a synergistic relationship—supportive leadership enhances teachers’ motivation, which in turn strengthens teacher’s performance. The novelty of this research lies in its comprehensive synthesis that maps empirical consistency and identifies research gaps within the vocational education context, particularly among Indonesian SMKs. The study contributes theoretically to vocational education management literature and provides practical recommendations for principals to implement adaptive leadership styles that enhance teachers’ motivation and performance.